Practical dyspnea assessment: relationship between the 0–10 numerical rating scale and the four-level categorical verbal descriptor scale of dyspnea intensity - Wysham, Nicholas G.; Miriovsky, Benjamin J.; Currow, David C.; Herndon, James E.; Samsa, Gregory P.; Wilcock, Andrew; Abernethy, Amy P. (Elsevier, 2015)
Context—Measurement of dyspnea is important for clinical care and research. Objectives—To characterize the relationship between the 0–10 Numerical Rating Scale (NRS) and four-level categorical Verbal Descriptor Scale (VDS) for dyspnea assessment. Methods—This was a substudy of a double-blind randomized controlled trial comparing palliative oxygen to room air for relief of refractory breathlessness in patients with life-limiting illness. Dyspnea was assessed with both a 0–10 NRS and a four-level categorical VDS over the one-week trial. NRS and VDS responses were analyzed in cross section and longitudinally. Relationships between NRS and VDS responses were portrayed using descriptive statistics and visual representations. Results—Two hundred twenty-six participants contributed responses. At baseline, mild and moderate levels of breathlessness were reported by 41.9% and 44.6% of participants, respectively. NRS scores demonstrated increasing mean and median levels for increasing VDS intensity, from a mean (SD) of 0.6 (±1.04) for VDS none category to 8.2 (1.4) for VDS severe category. The Spearman correlation coefficient was strong at 0.78 (P < 0.0001). Based on the distribution of NRS scores within VDS categories, we calculated test characteristics of two different cutpoint models. Both models yielded 75% correct translations from NRS to VDS; however, Model A was more sensitive for moderate or greater dyspnea, with fewer misses downcoded. Conclusion—There is strong correlation between VDS and NRS measures for dyspnea. Proposed practical cutpoints for the relationship between the dyspnea VDS and NRS are 0 for none, 1–4 for mild, 5–8 for moderate, and 9–10 for severe.